2012
DOI: 10.1111/jace.12130
|View full text |Cite
|
Sign up to set email alerts
|

Solute Diffusion of Platinum in Rutile Titanium Dioxide

Abstract: 195Pt solute diffusion coefficients in undoped single‐crystal rutile TiO2 have been determined parallel to the c‐axis over the temperature range of 1073–1523 K and oxygen partial pressure of 101 kPa. This has yielded the following temperature dependence: D195Pt=1.3±3.2×10−13m2s−1exp(−122.0±13.6italickJmol−1normalRT) On the basis of this result, it has been concluded that 195Pt diffuses via an interstitial mechanism involving rapid transport parallel to the c‐axis through open interstitial diffusion channels. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…1) However, AlN powders are very difficult to sinter without using a sintering aid such as Y 2 O 3 , CaO, or BaO.…”
Section: Introductionmentioning
confidence: 99%
“…1) However, AlN powders are very difficult to sinter without using a sintering aid such as Y 2 O 3 , CaO, or BaO.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, AlN is an attractive material for applications as an electrical packaging material and a component in structural composites. 1) It was recently shown that AlN powder can be used for preparation of alumina particles wrapped in few-layer graphene sheets, which are applicable for improving overall energy-conversion efficiency in dye-sensitized solar cells.…”
mentioning
confidence: 99%
“…Traditionally, AlN is used in packaging materials for electronic devices and as a large‐scale integrated circuit heat dissipation substrate, owing to its high thermal conductivity (~ 330 W/mK), low dielectric constant and loss, and high electrical insulation (> 10 14 Ω·cm) . Recently, rare earth‐doped AlN has been studied extensively as a new class of phosphor due to its high chemical stability and wide band gap (~ 6.2 eV) .…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, AlN is used in packaging materials for electronic devices and as a large-scale integrated circuit heat dissipation substrate, owing to its high thermal conductivity (~330 W/mK), low dielectric constant and loss, and high electrical insulation (> 10 14 Ω·cm). [4] Recently, rare earth-doped AlN has been studied extensively as a new class of phosphor due to its high chemical stability and wide band gap (~6.2 eV). [5] Several methods have been proposed for the preparation of AlN and AlON-based phosphors, such as high-energy ball milling, [6] spark plasma sintering, [7] gas pressure sintering, [8,9] carbothermal reduction-nitridation, [10,11] and gas reductionnitridation.…”
Section: Introductionmentioning
confidence: 99%